Case Report: Rare adverse events following CAR-T therapy in patients with relapsed/refractory diffuse large B-cell lymphoma - Shah, Ziniya; Kunwor, Ranju (Frontiers in Oncology, 2025)
Chimeric antigen receptor T-cell (CAR-T) therapy is a significant development in cancer therapy that is used to treat B-cell malignancies including B cell lymphoblastic leukemias, relapsed and refractory lymphomas, and multiple myeloma. CAR-T requires T-cell collection from the patient, which is genetically engineered to express a synthetic receptor that will bind to an antigen of a specific tumor. The CAR-T cells are then infused back into the patient, which function to attack the resistant cancer cells. Reported side effects of CAR-T include cytokine-release syndrome (CRS), macrophage activation syndrome (MAS), and immune effector cell-associated neurotoxicity syndrome (ICANS). Sometimes, patients can experience rare side effects which are not reported as often due to the rarity. We present a series of three patients with relapsed/refractory diffuse large B-cell lymphoma, who each received CAR-T therapy with Axicabtagene ciloleucel. Each patient developed unique and unprecedented adverse effects in the time following infusion of CAR-T. This includes manifestations of autoimmune demyelination and myelopathy, bullous dermatologic reactions on the lower extremities, and bilateral enlarged parotid glands as a result of CAR-T.